2016
DOI: 10.2214/ajr.15.15795
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Efficacy of 3-T MRI for Knee Injuries Using Arthroscopy as a Reference Standard: A Meta-Analysis

Abstract: This study does not provide evidence that 3-T scanners have superior diagnostic efficacy for meniscal damage and ACL integrity when compared with previous studies of 1.5-T machines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 49 publications
2
26
3
Order By: Relevance
“…Phelan et al summarized the results of 14 prospective studies and concluded that 2D sequences had a pooled sensitivity and specificity of 87% and 93%, respectively, for detecting ACL injuries . A recent meta‐analysis by Smith et al summarized the results of three studies performed using 3T MRI scanners and reported a pooled sensitivity and specificity for detecting ACL injuries of 92% and 99%, respectively . However, neither prior meta‐analyses found a significant improvement in diagnostic performance with the use of 3T scanners, which is in contrast with our findings.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Phelan et al summarized the results of 14 prospective studies and concluded that 2D sequences had a pooled sensitivity and specificity of 87% and 93%, respectively, for detecting ACL injuries . A recent meta‐analysis by Smith et al summarized the results of three studies performed using 3T MRI scanners and reported a pooled sensitivity and specificity for detecting ACL injuries of 92% and 99%, respectively . However, neither prior meta‐analyses found a significant improvement in diagnostic performance with the use of 3T scanners, which is in contrast with our findings.…”
Section: Discussioncontrasting
confidence: 93%
“…Furthermore, the comparison between the diagnostic performance of 3D sequences and simultaneously acquired 2D sequences revealed that both modalities have overall similar performance. Our pooled estimates of sensitivity and specificity of 3D sequences are also within the range of results of prior meta‐analyses, which reported sensitivity and specificity of 2D sequences for detecting ACL injuries . Phelan et al summarized the results of 14 prospective studies and concluded that 2D sequences had a pooled sensitivity and specificity of 87% and 93%, respectively, for detecting ACL injuries .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Smith et al . (2016) proved that there is no evidence that 3T scanners had superior diagnostic efficacy for ACL injury when compared with 1.5T machines 11 . Similarly, Phelan et al .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have compared the diagnostic accuracy of 1.5T MRI with 3.0T MRI 11 , MRI combined with ultrasonography 12 , and MRI combined with physical examination 8, 13 . However, the exact diagnostic accuracy of MRI for ACL injury is unknown, as are the differences in diagnostic accuracy between MRI with magnetic field intensities (MFI) greater than or equal to 1.5T compared with those below 1.5T, or between different MRI sequences, The objectives of this meta-analysis were to (i) systematically examine the diagnostic accuracy of MRI for the diagnosis of ACL injury; (ii) compare the diagnostic accuracy of MFI greater than or equal to 1.5T with MFI below 1.5T; and (iii) compare the diagnostic accuracy of different MRI sequences.…”
Section: Introductionmentioning
confidence: 99%